1991
DOI: 10.1017/s0022112091001477
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional cusped interfaces

Abstract: Two-dimensional cusped interfaces are line singularities of curvature. We create such cusps by rotating a cylinder half immersed in liquid. A liquid film is dragged out of the reservoir on one side and is plunged in at the other, where it forms a cusp at finite speeds, if the conditions are right. Both Newtonian and non-Newtonian fluids form cusps, but the transition from a rounded interface to a cusp is gradual in Newtonian liquids and sudden in non-Newtonian liquids. We present an asymptotic analysis near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 29 publications
9
90
1
1
Order By: Relevance
“…Free-surface flows are also very sensitive to the formation of cusp singularities (Joseph et al, 1991) even in seemingly innocuous flow situations. It seems as if surface tension should make the surface more regular, thus simplifying simulations.…”
Section: Simulationsmentioning
confidence: 99%
“…Free-surface flows are also very sensitive to the formation of cusp singularities (Joseph et al, 1991) even in seemingly innocuous flow situations. It seems as if surface tension should make the surface more regular, thus simplifying simulations.…”
Section: Simulationsmentioning
confidence: 99%
“…As the initial size of the bubble increases, the bottom edge becomes sharper and the cusp configuration is clearly observed. In particular, for the case of (d) R 0 = 30Δx, it is found that the cusp can be fitted to the functional form | x | 2/3 predicted by Joseph et al (28) for a two-dimensional cusp created by the flow induced in two counter-rotating cylinders.…”
Section: Journal Of Computational Science and Technologymentioning
confidence: 73%
“…This cuspidal tale occurs only in gas bubbles rising freely in non-Newtonian liquids. Joseph et al [8] defined the cuspidal tails as point singularities of curvature. They also stated that the build-up of extensional stresses near stagnation points may favor the formation of cusps.…”
Section: Fluid Mechanics Of Two-dimensional Cusping At the Trailing Ementioning
confidence: 99%